2022
DOI: 10.1038/s41586-022-05164-4
|View full text |Cite
|
Sign up to set email alerts
|

A phosphoinositide signalling pathway mediates rapid lysosomal repair

Abstract: Lysosomal dysfunction has been increasingly linked to disease and normal ageing 1 , 2 . Lysosomal membrane permeabilization (LMP), a hallmark of lysosome-related diseases, can be triggered by diverse cellular stressors 3 . Given the damaging contents of lysosomes, LMP must be rapidly resolved, although the underlying mechanisms are poorly understood. Here, using an unbiased proteomic approach, we show that LMP stimulates a phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
174
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(185 citation statements)
references
References 58 publications
7
174
4
Order By: Relevance
“…The latter two mechanisms appear to be independent (Niekamp et al, 2022), and both we and others (Tan & Finkel, 2022) have found that activation of the ESCRTand ER-mediated repair occurs independently of each other. However, independent activation mechanisms do not exclude the possibility that the alternative repair mechanisms cross-talk at some level.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The latter two mechanisms appear to be independent (Niekamp et al, 2022), and both we and others (Tan & Finkel, 2022) have found that activation of the ESCRTand ER-mediated repair occurs independently of each other. However, independent activation mechanisms do not exclude the possibility that the alternative repair mechanisms cross-talk at some level.…”
Section: Discussionsupporting
confidence: 54%
“…It also needs to be explained exactly how transfer of PS and cholesterol from the ER would mediate lysosome repair, and a relevant question is how the ER-mediated repair relates to the previously identified ESCRT- and ceramide-dependent repair mechanisms (Niekamp et al ., 2022; Radulovic et al ., 2018; Skowyra et al ., 2018). The latter two mechanisms appear to be independent (Niekamp et al ., 2022), and both we and others (Tan & Finkel, 2022) have found that activation of the ESCRT- and ER-mediated repair occurs independently of each other. However, independent activation mechanisms do not exclude the possibility that the alternative repair mechanisms cross-talk at some level.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This approach led to our recent discovery of the phosphoinositide‐initiated membrane tethering and lipid transport (PITT) pathway that is essential for rapid lysosomal membrane repair (Figure 1). 10 The PITT pathway is quickly triggered by LMP and it relies on new de novo membrane contacts between two organelles, namely damaged lysosomes and the endoplasmic reticulum (ER). In particular, we found that LMP stimulates rapid lysosomal recruitment of type II alpha phosphatidylinositol‐4 kinase (PI4K2A), leading to the production of phosphatidylinositol‐4‐phosphate (PtdIns4P, PI4P) on damaged lysosomes.…”
Section: Figurementioning
confidence: 99%